Intraoperative Fluorescence Is Useful but Not Always Sufficient in Contrast-Enhancing Malignant Gliomas - Moiyadi, Aliasgar V. (Indian Journal of Neurosurgery, 2018)
Fluorescence-guided resections have become standard of care for malignant gliomas. Strong fluorescence has been shown to correlate with solid enhancing tumor. However, with experience it has also been shown that visualized fluorescence may not identify the entire extent of the tumor. Knowing that malignant gliomas extend beyond the contrast-enhancing tumor seen on magnetic resonance imaging (MRI), reliance only on the fluorescence intraoperatively may not be enough. Intraoperative ultrasound is a readily available tool for real-time assessment of resection status, irrespective of the tumor type. We describe one such case in which after resecting all the visible fluorescing tumor component, we identified a significant component of nonfluorescing tumor, using intraoperative ultrasound that was further resected completely. This illustrates the need for multimodal intraoperative guidance for achieving optimal tumor resection in malignant gliomas.
Keywords: malignant gliomas; fluorescence; intraoperative ultrasound